PERANCANGAN TERMINAL TIPE A DI BOGOR DENGAN PENDEKATAN ARSITEKTUR NEO-VERNAKULAR - Melati Cyntia Utami; Sri Kurniasih (MAESTRO, 2019)
The application of Neo-Vernacular Architecture to the Design of Type A Terminals in Bogor can be interpreted as a place or building that serves to accommodate and serve the transportation needs of passengers from one place to another that applies the Neo-Vernacular building concept where buildings are made following local concepts but packaged modern. The design of Type A. Terminals in Bogor has been synthesized in the form of a design concept. This building plan seeks to provide a function of building public transportation facilities that are capable of serving passengers especially in the Bogor area. This terminal is designed with a Neo-Vernacular architecture approach that still has the image of the local area but the material used is able to adapt to its time.